Cognition and emotion : reviews of current research and theories - Houwer, Jan de.; Hermans, Dirk. (Psychology Press, 2010)
"Clearly written by international experts, this excellent book provides authoritative overviews of the most interesting and challenging debates in cognition and emotion. Both established researchers and students new to the field will warmly welcome such clear statements of what questions have already been asked, what controversies remain, and what the future of the field may hold." Mark Williams, Wellcome Principal Research Fellow & Professor of Clinical Psychology, University of Oxford, UK --